ALASAN DAN TUJUAN LAHIRNYA UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Khiyaroh (Hukum Keluarga Islam IAIN LANGSA, 2020)
This articles illustrate the process of maked the Marriage Law Number 1 of 1974 begins with government initiatives to discuss the scope of legislative. Government initiatives did not just emerge, but long before they were submitted to the legislative, the government received many inputs regarding marital regulations. Submission of revisions to the marriage regulations were mostly submitted by women's organizations. The process of the formation of the Marriage Law for approximately seven months, starting from the government submitting the Draft Law to the legislature until all factions declare approval article by article. From 77 Articles to 66 Articles to become legislation. But there are many contradictions when the law will be passed. Especially from the Islamic group namely PPP factions they stated that the articles in it violated many Islamic rules. while the faction of the work actually considers its articles to be appropriate. Namely with the article that has highlighted the position of the wife in the household. Another of the PDI factions who only highlighted the issue of polygamy and the principle of monogamy. After being approved and approved by the government the impact of polygamy and divorce decreases. While the problem of Siri marriage is even more widespread.